Teaching and learning in the 21st century: an overview / Johan Eddy Luaran ... [et al.] - Luaran, Johan Eddy; Jain, Jasmine; Alias, Roslinda; Embi, Roslani; Temyati, Zawawi (UiTM Press, 2019)
The proliferation of computers coupled with internet access placed a fundamental change to the history of humankind and United Nation report has recently declared that Internet access is a human right (United Nations, 2016). Technological devices not only changed the way we communicate with each other, but reshaped the way we lead our life on a daily basis to a point it becomes a necessity to the major global population. As educators, the questions that often we ask are: What effect do these technological devices bring to teaching and learning?